PERANAN KEPALA DESA DALAM MENINGKATKAN SUMBER DAYA APARATUR DESA DI KECAMATAN DEPATI VII KABUPATEN KERINCI - M.H, murlinus (journal of RESIDU, 2018)
This research uses qualitative approach, with descriptive method, data source is informant, place or location of research archives and documents, data collection techniques used are interviews, observation and document analysis. Based on the results of the research can be concluded that the potential owned by the village apparatus of depati vii sub-district is sufficient but it needs some improvements on the side of the depati village head vii held seminars, discussions once a month, with such confidence and trust the potential of the best village apparatus will be able to be achieved, it is expected to all the village heads in depati vii sub-district, for the future in implementing the village administration so that the village apparatus that is used to establish the work of the village head is at least a dii graduate, if it can be s1, it is all for the progress of the village the authors see this empowerment constrained the ability of the village head itself, there are still many village heads who lack understanding of the empowerment itself, so the district government should foster the village head first, so that the village head will be able to nurture the apparatus in their village.   Keywords: Roles, Resources